THE IMPORTANCE AND INCIDENCE OF FOOD BORN HELMINTH INFECTIONS IN MAN, IN IRAN - H.A. Neshat; A.H. Eslami (Tehran University of Medical Sciences, 1976)
A wide variety of helminth parasite, which is quite prevalent in Iran, can infect man by the oral route. The main sources of infections are meat, vegetables and water. Some of these parasites, e.g. Cysticercus bovis, C. cellulose, Trichinella spairalis and Anisakis larvae, are present in the tissue of food animal. Human infection establish by consuming raw or inadequately cooked pork, beef or fish. The infective stages of some helminths, e.g. Trichostrongylus spp., Ascaris lumbricoides, Trichuris trichura, Fasciola spp. Dicrocelium dendriticum and Dracuncwlus medinensis may infect man through vegetable and drinking water. Using human and animal manure as fertilizer of the soil, facilitate the transmission of these parasites to man. Contaminated food materials can pay also a role in, human hydatidosis. Hygiene is a key factor in the control of all conditions and both medical and veterinary professions have an important function in this field.